COVID-19 associated kidney impairment in adult: Qualitative and quantitative analyses with non-enhanced CT on admission. Issue 131 (October 2020) - Huang, Qiang; Li, Jian; Lyu, Shuangzhi; Liang, Wenjie; Yang, Rong; Zhang, Rui; Xiao, Wenbo; Liu, Jinpeng; Yan, Senxiang; Zheng, Liangrong; Chen, Feng
Highlights: Renal parenchyma attenuation on non-enhanced CT decreases in COVID-19. Renal parenchyma attenuation is negatively correlated with serum creatinine levels. Perinephric fat stranding suggests more severe renal impairment in COVID-19. Non-enhanced CT could be used in evaluation of COVID-19 associated renal impairment on admission. Abstract: Purpose: To qualitatively and quantitatively assess kidney imapairment in adults with COVID-19 by analysing imaging features on non-enhanced CT (NECT) and possible correlation between renal parenchymal attenuation (RPA) and serum creatinine (SCr) levels on admission. Methods: This study was approved by the local institutional ethics committee. A total of 82 patients with COVID-19 admitted from 10/1/2020∼15/3/2020 were enrolled. RPA and perinephric fat stranding (PFS) were evaluated on NECT imaging. According to the presence of PFS, the patients were divided into two groups: Group A, 38 patients with PFS, and Group B, 44 patients without PFS. Clinical data, including age, gender, clinical classification, SCr levels, and RPA on NECT were analysed. The RPA and SCr of the two groups with COVID-19 were analysed to determine possible difference and correlation. Eighty subjects with no kidney diseases were randomly selected as control group to determine the RPA of normal kidney performed on the same CT scanner. Results: Mean age, male to female ratio, number of severe and critical cases, and SCr of Group A were higher than those of Group B. Both mean RPA of Group A and Group B were lower than that of control. Mean RPA of Group A was even lower than that of Group B. A significant weak negative linear correlation between RPA on NECT and SCr in COVID-19 was indicated. Conclusions: Decrease in RPA on NECT was observed in patients with COVID-19 and a weak linear negative correlation with SCr levels was found. The presence of PFS suggested more severe renal impairment in COVID-19. RPA measurements and PFS could be useful in quantitative and qualitative evaluation of COVID-19 associated renal impairment on admission.